IMPLEMENTASI AKAD-AKAD PADA KOPERASI SYARIAH : Perbedaan Antara Koperasi Syariah Dan Koperasi Konvensional - Muhammad Miftahul Ikhsan (KASBANA, 2024)
Sharia Cooperatives in Fatwa DSN Number 14 concerning Guidelines for the Establishment and Operation of Sharia Cooperatives in 2021 that sharia cooperatives are cooperatives that are created, managed, and run their businesses in accordance with sharia principles. This type of research uses literature research that takes data through information by obtaining library materials, data techniques that have been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. Looking at the comparison related to the differences between conventional cooperatives and sharia cooperatives, it is very clear that sharia cooperatives have a prudent nature, where starting from supervisors who are competent related to sharia cooperatives, carrying out a profit-sharing system not based on interest, cooperation with sharia banks, raising funds that can be deposited can also be in the form of term savings. The distribution of funds is broader in focus on whether you want to make loans only, whether to do cooperation, or to carry out buying and selling, and has a social nature that can distribute Ziswaf funds to the community. Legal Basis of Sharia Cooperatives Article 87 paragraphs 3 and 4 of Law of the Republic of Indonesia Number 17 of 2012, Fatwa DSN MUI Number 141 of 2021 concerning Guidelines for the Establishment and Operation of Sharia Cooperatives. contracts used in sharia cooperatives such as:, Ba'i Al-Murabahah, Ba'i Al-Salam, Ba'i Al-Istishna, Ijarah, Shirkah, Wadi'ah, Qardh.